Improving access to diagnostics: an evaluation of a satellite laboratory service in the emergency department. Issue 4 (18th June 2004) - Leman, P; Guthrie, D; Simpson, R; Little, F
Abstract : Objectives: To measure the impact of a satellite laboratory upon laboratory result turnaround times and clinical decision making times. Design: A prospective cohort study, the intervention group had blood tests sent Monday to Friday 12 noon to 8 pm and the control group had blood tests sent outside these hours. The data were collected over a six week period before the laboratory was opened, and a subsequent six week period. Setting: An urban teaching hospital emergency department. Participants: 1065 patients requiring blood tests. Main outcome measure: Time from the blood sample being sent to the laboratory to the results being available on the clinician's computer. Results: The time to haematology (blood count) results in the intervention group decreased by 47.2 minutes (95% CI 38.3 to 56.1, p<0.001) after the laboratory was opened. The corresponding control group times were unchanged (0.6 minutes; −13.8 to 15.0, p = 0.94). Similar sized differences were also seen for haemostasis (d -dimer) testing 66.1 (41.8 to 90.4) minutes compared with −14.2 (−47.1 to 18.7) and chemistry 41.3 (30.3 to 52.2) compared with −4.2 (−17.4 to 8.9) testing. Decisions to discharge patients were significantly faster (28.2 minutes, 13.5 to 42.8, p<0.0001) in the intervention group after the laboratory was opened (controls; −2.6 minutes −27.0 to 21.7). No change was seen with decisions to admit patients. There was a trend for earlier laboratory results modifying intravenous drug or fluids orders, or both (p = 0.06) Conclusion: A comprehensive satellite laboratory service is an important adjunct to improve the timeliness of care in the emergency department.